Penerapan Konsep EVA sebagai Added Approach dari Analisis Rasio Keuangan untuk Mengukur Kinerja PT Gudang Garam di Kediri - Mulia, Teodora Winda (Jurnal Widya Manajemen & Akuntansi, 2002)
Financial ratio analysis as a measure of company's performance is commonly made a bias lo investors and stockholders. In order to reduce analysis risk error, EVA is used as added approach to traditional approach (Financial ratio analysis). In this case, EVA is relevant to measure management performance, which is based on certain periodic value added. If financial ratio becomes the only tool in measuring company's performance, it appears to be a good performance, but actually there is neither increase nor decrease.